A COMPREHENSIVE REVIEW OF PULSE OXIMETRY: OPTICAL PRINCIPLES, SIGNAL PROCESSING, AND CLINICAL APPLICATIONS - Muhammad Faiq Syarifun Najih (Khamdan Karya Cipta, 2026)
Pulse oximetry has become one of the most widely used non-invasive technologies for monitoring arterial oxygen saturation (SpO₂) in clinical and home healthcare settings. Despite its widespread adoption, measurement accuracy is strongly influenced by the underlying optical principles, signal processing techniques, and physiological characteristics of the measured tissue. This study aims to comprehensively analyze the physical principles governing pulse oximetry from an electromedical physics perspective. A narrative literature review approach was employed by synthesizing recent scientific publications addressing optical absorption, the Beer–Lambert law, photoplethysmography (PPG), signal processing, and factors affecting measurement accuracy. The analysis demonstrates that pulse oximetry operates through the integration of differential light absorption at red (660 nm) and near-infrared (940 nm) wavelengths with pulsatile blood volume detection using photoplethysmography. The ratio-of-ratios algorithm enables non-invasive estimation of arterial oxygen saturation while minimizing the influence of tissue thickness and optical path variations. However, measurement performance remains susceptible to motion artifacts, ambient light interference, peripheral hypoperfusion, abnormal hemoglobin species, and skin pigmentation, which may introduce clinically significant bias. Recent technological developments, including multi-wavelength optical sensing, advanced digital signal processing, artificial intelligence, and Internet of Things (IoT)-based monitoring systems, provide promising approaches for improving measurement accuracy, robustness, and remote patient monitoring capabilities. In conclusion, a comprehensive understanding of optical physics and signal processing principles is essential for optimizing pulse oximeter performance and supporting the development of more accurate, reliable, and inclusive electromedical devices for future healthcare applications.